Current assumptions for quantitative microbial risk assessment (QMRA) of Norovirus contamination of drinking water catchments due to recreational activities: an update. (6th October 2022) - Deere, Dan; Ryan, Una
Abstract: Contamination of drinking water from Norovirus (NoV) and other waterborne viruses is a major public health concern globally. Increasingly, quantitative microbial risk assessment (QMRA) is being used to assess the various risks from waterborne pathogens and evaluate control strategies. As urban populations grow and expand, there is increasing demand for recreational activities in drinking water catchments. QMRA relies on context-specific data to map out the pathways by which viruses can enter water and be transferred to drinking water consumers and identify risk factors and appropriate controls. This review examines the current evidence base and assumptions for QMRA analysis of NoV and other waterborne viral pathogens and recommends numerical values based on the most recent evidence to better understand the health risks associated with recreators in Australian drinking water sources; these are broadly applicable to all drinking water sources where recreational access is allowed. Key issues include the lack of an agreed upon data and dose-response models for human infectious NoV genotypes, faecal shedding by bathers, the extent of NoV infectivity and aggregation, resistance (secretor status) to NoV and the extent of secondary transmission. HIGHLIGHTS: A review of quantitative microbial risk assessment (QMRA) is performed for determining public health risk from drinking water sources contaminated with Norovirus (NoV) by recreational activities. A review of NoV epidemiological data is performed for the purpose of exposure assessment, dose-response and risk assessment. Key recommendations and guidelines for numerical values are developed for the purpose of QMRA analysis. Graphical Abstract